Rare Causes of Acute Coronary Syndrome: Carbon Monoxide Poisoning - Raluca Ecaterina Haliga; Bianca Codrina Morărașu; Victorița Șorodoc; Cătălina Lionte; Oana Sîrbu; Alexandra Stoica; Alexandr Ceasovschih; Mihai Constantin; Laurentiu Șorodoc (Life, 2022)
Acute coronary syndrome (ACS) is a spectrum of clinical and paraclinical disorders arising from an imbalance of oxygen demand and supply to the myocardium. The most common cause is atherosclerosis; however, other rare causes such as carbon monoxide (CO) poisoning should be considered. Through tissue hypoxia and direct cell injury, CO poisoning can lead to a broad spectrum of cardiac disorders, especially ACS. Materials and Methods. We have conducted a retrospective study in the Toxicology Department of Saint Spiridon Emergency University Hospital, including all patients admitted through the emergency department with CO poisoning. We divided the cohort into event group (myocardial injury) and non-event group (patients without myocardial injury) and performed a subset analysis of the former. Results. A total of 65 patients were included, 22 in the event and 43 in the non-event group. The severity of poisoning did not correlate with myocardial injury; however, 50% of the event group had severe poisoning with carboxyhaemoglobin ≥ 20%. Cardiac enzyme markers (troponin and creatin-kinase MB) had a statistically significant increase in the event group compared to the non-event group (p < 0.05). Most of the patients in the STEMI (50%) and NSTEMI (66.7%) groups had severe CO intoxication. The STEMI group had a mean age of 27.7 years old and no comorbidities. Conclusions. Myocardial injury can develop in CO poisoning irrespective of the severity of poisoning, and it can be transient, reversible, or permanent. Our study introduces new information on adverse cardiac events in patients with CO poisoning, focusing on the ACS. We found that the severity of CO poisoning plays an important role in developing myocardial injury, as 50% of patients in the event group were severely intoxicated. While in-hospital mortality in our study was low, further prospective studies should investigate the long-term mortality in these patients.